Analisis Efisiensi Teknis Usahatani Cabai Rawit (Capsicum Frustescens) Di Desa Ngantru, Kecamatan Ngantang, Kabupaten Malang - Riska Melati Agustina; Rini Mutisari; Tri Wahyu Nugroho; Deny Meitasari (Department of Agricultural Social Economics, Faculty of Agriculture, Brawijaya University, 2023)
The aims of this research on technical efficiency analysis of chili pepper farming in Ngantru Village are to analyze the production factors that affect the production of chili pepper, the level of technical efficiency, and the factors that cause the technical inefficiency. This research uses Stochastic Frontier Analysis (SFA). The sample calculation uses the Parel formula, obtained as many as 40 respondents. The results showed that there were 5 production factors that had a significant effect on the production of chili pepper, land area and manure with coefficients of 0.230 and 0.386 with α = 5%, labor with coefficients of 0.192 with α = 10%, seeds and chemical fertilizers with coefficient of 0.193 and 0.159 with α = 15%. On average, chili pepper farmers in Ngantru Village are not technically efficient with the average of technical efficiency value at 0.67, with a maximum value of 0.995 and a minimum value of 0.34. Socio-economic factors that affect technical inefficiency are the level of education, experience, age, and agricultural extention. Education and experience have a significant effect on α = 5% with a negative coefficient. Agricultural extension has a significant effect on α = 10% with a negative coefficient sign, which means that education, experience and counseling can increase the level of technical efficiency. While the age factor has a significant effect on α = 5% with a positive coefficient, which means that the age factor of farmers can increase technical inefficiency.